Novel WWOX deleterious variants cause early infantile epileptic encephalopathy, severe developmental delay and dysmorphism among Yemenite Jews. (May 2019) - Weisz-Hubshman, M.; Meirson, H.; Michaelson-Cohen, R.; Beeri, R.; Tzur, S.; Bormans, C.; Modai, S.; Shomron, N.; Shilon, Y.; Banne, E.; Orenstein, N.; Konen, O.; et al.
Abstract: The human WW Domain Containing Oxidoreductase (WWOX ) gene was originally described as a tumor suppressor gene. However, recent reports have demonstrated its cardinal role in the pathogenesis of central nervous systems disorders such as epileptic encephalopathy, intellectual disability, and spinocerebellar ataxia. We report on six patients from three unrelated families of full or partial Yemenite Jewish ancestry exhibiting early infantile epileptic encephalopathy and profound developmental delay. Importantly, four patients demonstrated facial dysmorphism. Exome sequencing revealed that four of the patients were homozygous for a novel WWOX c.517-2A > G splice-site variant and two were compound heterozygous for this variant and a novel c.689A > C, p.Gln230Pro missense variant. Complementary DNA sequencing demonstrated that the WWOX c.517-2A > G splice-site variant causes skipping of exon six. A carrier rate of 1:177 was found among Yemenite Jews. We provide the first detailed description of patients harboring a splice-site variant in the WWOX gene and propose that the clinical synopsis of WWOX related epileptic encephalopathy should be broadened to include facial dysmorphism. The increased frequency of the c.517-2A > G splice-site variant among Yemenite Jews coupled with the severity of the phenotype makes it a candidate for inclusion in expanded preconception screening programs. Highlights: Dysmorphic features can be part of the clinical signs of WWOX related EIEE. A genotype–phenotype correlation is suggested in WWOX related disorders. The WWOX splice-site variant c.517-2A > G has an increased carrier rate among Yemenite Jews.